Dampak Non-Evidence-Based Policy terhadap Penanganan Banjir di Kabupaten Aceh Singkil - Fauzan Hidayat (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
This study aims to investigate the impact of non-evidence-based policies on flood management in Aceh Singkil, where yearly flood had increased despite recommendations from the Ministry of Public Works and Public Housing. The main recommendation, building flood control embankments, was dropped by new local leaders, who instead chose river dredging despite its lack of scientific support. To achieve this objective, a qualitative case study method was used. Data were gathered through in-depth interviews with stakeholders, including government officials, experts, and affected residents, as well as through analysis of government reports and academic sources. The data were subsequently analyzed using triangulation methods to ensure validity and reliability. Furthermore, the political dynamics and impacts of these policy changes were explored, emphasizing how ignoring evidence-based solutions could lead to more severe floods and greater socioeconomic losses. The results showed that the river dredging policy in Aceh Singkil, shaped more by political interests than technical studies, proved ineffective in reducing flood. Instead, it offered only a temporary fix, increased socioeconomic losses, and disregarded the principles of evidence-based disaster mitigation and long-term sustainability.